2013
DOI: 10.1007/s11159-013-9354-4
|View full text |Cite
|
Sign up to set email alerts
|

Why should I read? - A cross-cultural investigation into adolescents’ reading socialisation and reading attitude

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
0
24
0
1
Order By: Relevance
“…Since it is really the implicit norm (e.g., observing parents reading, visiting the library) rather than explicit norms (e.g., parents telling child to read) that counts for encouraging reading students (Broeder and Stokmans 2013), the survey questions focused on what kinds of reading practices students observed at home to understand their home reading practices.…”
Section: Survey Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is really the implicit norm (e.g., observing parents reading, visiting the library) rather than explicit norms (e.g., parents telling child to read) that counts for encouraging reading students (Broeder and Stokmans 2013), the survey questions focused on what kinds of reading practices students observed at home to understand their home reading practices.…”
Section: Survey Findingsmentioning
confidence: 99%
“…In a comparative study of the reading practices of the Netherlands, China and South Africa, Broeder and Stokmans (2013) discovered that despite cultural and situational differences between the countries, one of the most important determinants for reading was a hedonic reading attitude, or the habit of reading for leisure. What this tells us is that one key factor for successful reading programmes is getting students to want to read, and not only read when they are told to.…”
Section: Introductionmentioning
confidence: 99%
“…Gender showed some differences but only with respect to subjective measures [5]. Girls were a bit more positive about their reading proficiency; boys were slightly more positive about their performance on the task.…”
Section: -P5 Shs Web Of Conferencesmentioning
confidence: 87%
“…The first two concern our adaptation of the PIRLS approach [2,3]. The third is related to the empirical embedding of the instrument [4,5]. The first question is whether it is possible to test literary understanding using a short passage from a (larger) novel.…”
Section: Research Questionsmentioning
confidence: 99%
“…A 30-year study by Scarborough and Dobrich (1994) identified correlations between attitudes toward reading and the extent of early literacy development. Also important is the amount of reading an individual completes, with positive attitude toward reading, and the development of highly motivated readers being two important consequences (Applegate & Applegate, 2004;Broeder, & Stokmans, 2013;Cunningham & Stanovich, 1997;Cunningham, Perry, Stanovich & Stanovich, 2004;Sainsbury & Schagen, 2004;Schaffner, Schiefele, & Ulferts, 2013 A reader's motivation is also influenced by the choice of texts available to them (Paris & Carpenter, 2004). Studies into reading practices have noted a decline in children's reading for pleasure across all age groups, as well as an increase in negative attitudes toward reading in general (e.g.…”
Section: The Purposes Of Children's Literaturementioning
confidence: 99%